Glycemic Index Diversity Among Seven Banggai Yams: Evidence from the Incremental Area Under the Curve Method - Marselina Sattu; Sandy Novryanto Sakati; Lisa Salsa Handayani; Maria Kanan; Rekhal Febrianty; Muh. Riski K Deko (Journal of Health and Nutrition Research, 2026)
Banggai yam (Dioscorea sp.) is an indigenous carbohydrate source in Central Sulawesi with potential value for functional-food development. However, comparative glycemic index (GI) data for local Banggai yam varieties remain limited. This study aimed to determine the GI of seven Banggai yam varieties using the incremental area under the curve (iAUC) approach based on ISO 26642:2010 principles. The study used a parallel-group design with paired reference-food testing. Seventy healthy adults were allocated to seven groups (n=10 per variety). Each participant completed two test sessions after an overnight fast: a glucose reference food equivalent to 50 g anhydrous glucose and one assigned steamed yam portion containing 50 g available carbohydrate. Capillary blood glucose was measured at 0, 15, 30, 60, and 120 minutes. The calculated GI values showed clear variation across varieties. Bunggon (61.5), Ateno (63.91), Boan (67.7), and Tuu (67.8) were classified as moderate-GI varieties, whereas Pusus (87.3), Sombok (94.4), and Pasandil (95.44) were classified as high-GI varieties. The consolidated glucose-response curves also indicated more attenuated postprandial responses for Ateno and Tuu than for the high-GI varieties. These findings indicate that Banggai yam exhibits substantial inter-varietal diversity in glycemic response. Moderate-GI varieties, particularly Bunggon and Ateno, are promising raw materials for Banggai yam–based food products intended to provide a lower glycemic impact than the high-GI varieties